The UNPC innovativeness set of indicators for idea or project selection and maturation in healthcare. Issue 3 (2nd October 2017) - Yannou, Bernard; Farel, Romain; Cluzel, François; Bekhradi, Alborz; Zimmer, Benjamin
Abstract: A great deal of work has been done to characterize entire sets of ideation indicators as well as isolated factors of innovativeness . Nevertheless, entire sets of innovativeness indicators are essential in business innovation competitions, as well as within companies in order to select promising innovation seeds. In this paper, a complete set of innovativeness indicators in the context of innovating in healthcare is proposed. The UNPC innovativeness model, standing for usefulness, newness, profitability and (proof of) concept, has been tested and validated over a period of 4 years within the largest European innovation cluster in the silver economy. Four authentic examples of innovation selections are analyzed. They illustrate how the UNPC model is able to provide clear and efficient guidance for better decision-making in the context of innovating for the elderly. In addition, a framework for monitoring an innovative idea or project, and for increasing its maturity, is proposed. The UNPC monitoring process starts with the Strengths, Weaknesses, Opportunities, and Threats analysis of competing ideas. It then becomes dynamic, looking for new evidence for increasing the certainty and impact of UNPC proofs of the competing ideas. The model has been successfully used for upgrading a popular smart application on activity tracking.